INVESTIGATION ON GEOMETRICAL STRUCTURE AND DOPING CONCENTRATION OF POWER DMOS FOR SPACE ENVIRONMENT APPLICATIONS - YAHYA, ERMAN AZWAN (2019)
The inherent characteristics of power DMOS for high frequency application makes the device very important especially for switching device operation. However, the implementation of the power DMOS in harsh environment especially for space application requires the device to withstand radiation effects. This could have resulted in high electric field stress introduced in the power DMOS structure at JFET region. In this research, a new radiation hardened technique is proposed by modifying the Junction Field Effect Transistor (JFET) region in the device structure and the SEE phenomena effects are analysed by using “reliability test tool” in software simulation. Based on simulation results, the electrical characteristics of proposed and conventional design are approximately 95% similar. The average different margin between both designs also very less and it is about 0.5% for output characteristic and around 1% for the transfer characteristic.